Generation and Characterization of a Novel Angelman Syndrome Mouse Model with a Full Deletion of the Ube3a Gene - Syding, Linn Amanda; Kubik-Zahorodna, Agnieszka; Nickl, Petr; Novosadova, Vendula; Kopkanova, Jana; Kasparek, Petr; Prochazka, Jan; Sedlacek, Radislav (Cells, 2022)
Angelman syndrome (AS) is a neurodevelopmental disorder caused by deficits in maternally inherited UBE3A. The disease is characterized by intellectual disability, impaired motor skills, and behavioral deficits, including increased anxiety and autism spectrum disorder features. The mouse models used so far in AS research recapitulate most of the cardinal AS characteristics. However, they do not mimic the situation found in the majority of AS patients who have a large deletion spanning 4-6 Mb. There is also a large variability in phenotypes reported in the available models, which altogether limits development of therapeutics. Therefore, we have generated a mouse model in which the Ube3a gene is deleted entirely from the 5' UTR to the 3' UTR of mouse Ube3a isoform 2, resulting in a deletion of 76 kb. To investigate its phenotypic suitability as a model for AS, we employed a battery of behavioral tests directed to reveal AS pathology and to find out whether this model better mirrors AS development compared to other available models. We found that the maternally inherited Ube3a-deficient line exhibits robust motor dysfunction, as seen in the rotarod and DigiGait tests, and displays abnormalities in additional behavioral paradigms, including reduced nest building and hypoactivity, although no apparent cognitive phenotype was observed in the Barnes maze and novel object recognition tests. The AS mice did, however, underperform in more complex cognition tasks, such as place reversal in the IntelliCage system, and exhibited a different circadian rhythm activity pattern. We show that the novel UBE3A-deficient model, based on a whole-gene deletion, is suitable for AS research, as it recapitulates important phenotypes characteristic of AS. This new mouse model provides complementary possibilities to study the Ube3a gene and its function in health and disease as well as possible therapeutic interventions to restore function.
Keywords: poruchy autistického spektra; 5' nepřekládaná oblast; Angelman syndrome; Autism Spectrum Disorder; neurodevelopmental disease; Disease Models, Animal; autism spectrum disorder; Mice; ubikvitinligasy; 5' Untranslated Regions; Ubiquitin-Protein Ligases; modely nemocí na zvířatech; zvířata; 3' nepřekládaná oblast; Angelman Syndrome; mouse model; myši; 3' Untranslated Regions; UBE3A; Angelmanův syndrom; Animals